On the semantics of subordinate clauses of time - Pajėdienė, Jūratė (Lietuvių kalba, 2008)
The paper sets out to discuss the correlation between the semantic relationships of de re and de dicto type of subordinate clauses of time and grammatical tense forms of predicates. The de dicto type of subordinate clauses is seen as correlating with the predicate expressed by the present and future tense forms of the verb and the usage of conjunctive words in the most general temporal meaning (kai/kada/kuomet/kol ‘when/while’). The above grammatical features of predicates and lexical preferences of conjunctive words usually determine that the meaning in the clauses of time is intertwined with other meanings. Preference to clauses of time over conditional clauses in particular discourses is mostly concerned with a well-developed communicative competence of the addressor. Displacing syntactic roles of components in a subordinate clause of time is only possible in very rare cases when reference is made to an idiosyncratic context of the situation of utterance.